Best Practice Recommendations for Stroke Patients with Dysphagia: A Delphi-Based Consensus Study of Experts in Turkey-Part I: Management, Diagnosis, and Follow-up - (:unkn) unknown (SPRINGER, 2022)
Dysphagia is one of the most common and important complications of stroke. It is an independent marker of poor outcome after acute stroke and may become chronic after the acute period and continues to affect all aspects of the patient's life. Patients with stroke may encounter any of the medical branches in the emergency room or outpatient clinic, and as in our country, there may not be specialists specific for dysphagia, such as speech-language pathologists (SLP), in every hospital. This study aimed to raise awareness and create a common opinion of medical specialists for stroke patients with dysphagia. This recommendation paper has been written by a multidisciplinary team and offers 45 recommendations for stroke patients with dysphagia. It was created using the eight-step Delphi round via e-mail. This study is mostly specific to Turkey. However, since it contains detailed recommendations from the perspective of various disciplines associated with stroke, this consensus-based recommendation paper is not only a useful guide to address clinical questions in practice for the clinical management of dysphagia in terms of management, diagnosis, and follow-up, but also includes detailed comments for these topics.
Keywords: Dysphagia; Stroke; Recommendation; Delphi study; Management; Diagnosis; Follow-up; ACUTE ISCHEMIC-STROKE; HEALTH-CARE PROFESSIONALS; VISCOSITY SWALLOW TEST; OROPHARYNGEAL DYSPHAGIA; ASPIRATION PNEUMONIA; 2018 GUIDELINES; RISK-FACTORS; REHABILITATION; BEDSIDE; RECOVERY